1995
DOI: 10.1093/carcin/16.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reducing compounds on the formation of DNA—protein cross-links in HL-60 cells induced by hexavalent chromium

Abstract: The influence of reducing compounds on the formation of DNA--protein cross-links induced by hexavalent chromium was studied in the human cell line HL-60. Analysis of cytoplasmic concentration of ascorbic acid and glutathione by HPLC in these cells showed that ascorbic acid was not detectable (detection limit: 0.1 nmol). The cellular content of glutathione was low (6 nmol/million cells). It could easily be depleted with diethylmaleate. The effect of glutathione, ascorbic acid and ascorbyl palmitate alone, or gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Asc plays a dominant role in reductive activation of Cr(VI) in vivo , and it has been found to strongly enhance apoptotic, genotoxic, and mutagenic effects of Cr(VI) in human and rodent cells , . However, the role of this key reducer in the production of DPC by Cr(VI) remains poorly understood as previous studies attempted to deliver Asc into cells through inefficient approaches , that are associated with significant side effects . Under Asc-deficient culture conditions, human cells largely rely on GSH for Cr(VI) reduction .…”
Section: Resultsmentioning
confidence: 99%
“…Asc plays a dominant role in reductive activation of Cr(VI) in vivo , and it has been found to strongly enhance apoptotic, genotoxic, and mutagenic effects of Cr(VI) in human and rodent cells , . However, the role of this key reducer in the production of DPC by Cr(VI) remains poorly understood as previous studies attempted to deliver Asc into cells through inefficient approaches , that are associated with significant side effects . Under Asc-deficient culture conditions, human cells largely rely on GSH for Cr(VI) reduction .…”
Section: Resultsmentioning
confidence: 99%
“… 77 Capellmann et al found that vitamin C reacted much faster with Cr(VI) at physiological pH than GSH did, suggesting an influence of the reaction velocity of the redox reaction between Cr(VI) and the reducing compounds on the toxification of Cr(VI) and formation of DPCs. 78 …”
Section: Chromium-carcinogenicity Chemopreventionmentioning
confidence: 99%
“…During this process, GSH may become reactive and bind to DNA [43,44]. Indeed, Cr (VI)-induced DNA-protein cross links increase in proportion to increasing GSH concentrations in cultured cells and cell-free systems [43,45,46]. When HP2 is present, the reduction of Cr (VI) by GSH also produces 0 2 0 and oOH, apurinic/apyrimidinic (AP) sites and DNA single-strand breaks [5,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%